The Case of Jahi McMath: A Neurologist's View - Shewmon, D. Alan (The Hastings Center report, 2018)
From the start, I followed the case of Jahi McMath with great interest. In December 2013, she clearly fulfilled the diagnostic criteria for brain death. As a neurologist with a special interest in chronic brain death, I was not surprised that, after she was flown to New Jersey, where she became statutorily resurrected and was treated as a comatose patient, Jahi's condition quickly improved. In 2014, her family reported that she sometimes responded to simple motor commands. I shared the general skepticism regarding these reports, assuming that the family was in denial and was misinterpreting spinal myoclonus (a rapid, involuntary twitch generated by the spinal cord) as volitional. The family had noticed that when Jahi's heart rate was above eighty beats per minute, she was more likely to respond, as though the heart rate reflected some sort of inner level of arousal. So they began to make video recordings. I have been privileged to be entrusted with copies of these recordings, forty-eight of which proved suitable for assessing alleged responsiveness. All have been certified by a forensic video expert as unaltered. The first thing that struck me was that the great majority of the alleged responses were not spinal myoclonus. In fact, they did not resemble any type of spontaneous, involuntary movement described in patients paralyzed from high spinal cord lesions.